Motives for Studying and Student Wellbeing: Validation of the Motivational Mindset Model - Hudig, Job; Scheepers, Ad W. A.; Schippers, Michaéla C.; Smeets, Guus (Frontiers in Psychology, 2021)
Research on the joint effect of multiple motives for studying was recently given a push in a new direction with the introduction of the motivational mindset model. This model contributes to a better understanding of study success and student wellbeing in higher education. The aim of the present study is to validate the newly developed model and the associated mindset classification tool. To this end, 662 first-year university students were classified in one of the four types of motivational mindset using the classification tool and three exploratory validation procedures were conducted through sense of purpose, study engagement, and students’ background characteristics in terms of gender and ethnicity. Both purpose and study engagement are central dimensions of student wellbeing and predictors of study success. The results show that (1) sense of purpose and study engagement differ across the four types of mindset, (2) students in the low-impact mindset show the least optimal pattern of study engagement and sense of purpose, (3) sense of purpose and study engagement are positively related and this relationship is consistent across mindsets, (4) overall differences in purpose and study engagement between gender and ethnic subgroups stem from one specific type of motivational mindset. The results provide support for the validity of the motivational mindset model and the usefulness of the mindset classification tool. The implications of the findings are discussed as well as promising avenues for future research.